ClickArr: a novel, high-throughput assay for evaluating β-arrestin isoform recruitment - French, Alexander R.; Meqbil, Yazan J.; van Rijn, Richard M. (Frontiers in Pharmacology, 2023)
BACKGROUND: Modern methods for quantifying signaling bias at G protein-coupled receptors (GPCRs) rely on using a single beta-arrestin isoform. However, it is increasingly appreciated that the two beta-arrestin isoforms have unique roles, requiring the ability to assess beta-arrestin isoform preference. Thus, methods are needed to efficiently screen recruitment of both beta-arrestin isoforms as they compete for a target GPCR in cells. METHODS: We used molecular cloning to develop fusion proteins of the d opioid receptor (DOR), beta-arrestin 1, and beta-arrestin 2 to fragments of click beetle green and click beetle red luciferases. In this assay architecture, recruitment of either beta-arrestin 1 or 2 to the DOR generates a spectrally distinct bioluminescent signal, allowing us to co-transfect all three constructs into cells prior to agonist challenge. RESULTS: We demonstrate that our new assay, named “ClickArr”, is a live-cell assay that simultaneously reports recruitment of both beta-arrestin isoforms as they compete for interaction with the DOR. We further find that the partial DOR agonist TAN67 has a significant efficacy bias for beta-arrestin 2 over beta-arrestin 1 when recruitment is normalized to the reference agonist leu-enkephalin. We confirm that ClickArr reports this bias when run either as a high-throughput end point or high-throughput kinetic assay, and cross-validate this result using the PathHunter assay, an orthogonal commercial assay for reporting beta-arrestin recruitment to the DOR. CONCLUSIONS: Our results suggest agonist:GPCR complexes can have relative beta-arrestin isoform bias, a novel signaling bias that may potentially open up a new dimension for drug development.